2019
DOI: 10.1016/j.apradiso.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of renal arsenic accumulation using images based on X-ray fluorescence at the tissue, cellular, and subcellular levels

Abstract: Exposure to arsenic (As) through drinking water results in accumulation of As and its methylated metabolites in several organs, promoting adverse health effects, particularly potential development of cancer. Arsenic toxicity is a serious global health concern, since over 200 million people are chronically exposed worldwide, Abundant biochemical and epidemiological evidence indicates that the kidney is an important site of uptake and accumulation of As, and mitochondrial damage plays a crucial role in arsenic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…An increasing body of evidence supports that the kidney is a primary site of arsenic uptake and accumulation. Recently, X-ray fluorescence spectrometry allowed detection of arsenic accumulation, specifically at level of the kidney cortex [51]. X-ray fluorescence spectrometry may provide comprehensive information of bioaccumulation for biomedical and toxicological research by allowing direct measurement of the distribution of arsenic at tissue, cellular, and subcellular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing body of evidence supports that the kidney is a primary site of arsenic uptake and accumulation. Recently, X-ray fluorescence spectrometry allowed detection of arsenic accumulation, specifically at level of the kidney cortex [51]. X-ray fluorescence spectrometry may provide comprehensive information of bioaccumulation for biomedical and toxicological research by allowing direct measurement of the distribution of arsenic at tissue, cellular, and subcellular level.…”
Section: Discussionmentioning
confidence: 99%
“…Next, X-ray absorption spectroscopy has been shown to allow in vivo assessment of whole-body distribution, which is key information for the development of chelation therapies [52]. Future studies using these analytical methods may provide essential research data to understand the sequence of specific mechanisms of nephrotoxicity and deepen the understanding of the association between long-term arsenic exposure and kidney damage [51].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed the potential of such a system for biological sample mappings. [18,19] Detailed features and analytical conditions are displayed in Table 2. Spectral data from EDXRF analysis were evaluated using the WinFTM software, version 6.35 linked to the instrument.…”
Section: Instrumentationmentioning
confidence: 99%
“…Depending on the synchrotron beamline, imaging can be performed with lateral resolution down to 20 nm and, in case of XAS spectroscopy, down to 50 nm [103]. Typically, samples are analyzed at 50-100 µm sections [117,118,127]. Moreover, this technique offers the possibility to analyze the samples in hydrated state; therefore, no elaborated sample preparation such as resin embedding is required.…”
Section: Synchrotron-based Xrf (X-ray Fluorescence Spectroscopy)mentioning
confidence: 99%